Mountain hospitals in the Veneto Alps and Pre-Alps in the late Middle Ages (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The charitable and welfare institutions in the Veneto mountains have left documentary evidence from the 12th century onwards. These sources concern hospitals and confraternities founded both in the episcopal cities of Belluno and Feltre and in the small villages located in the northernmost area of the Veneto, in a territorial context where collective efforts to offer help to both needy travellers and poor residents seem to prevail over initiatives that go back to individuals, noblemen and civic or ecclesiastical bodies.
Keywords: Middle Ages; Mountain; Veneto; Belluno; Feltre; Cadore; Hospital; Community; Welfare; Confraternity